Trends and problems of higher education in Ukraine in contemporary conditions - Budanov, Volodymyr; Rodionov, Viktor (Human Geography Journal, 2023)
The war in Ukraine, which began as a full-scale war on February 24, 2022, destroyed the usual rhythm of existence, led to severe destabilization in all areas of the country’s life, disoriented the majority of the population, and raised questions about the search for ways to survive. Education is one of the most vulnerable areas of the socio-economic sphere. This is due, first of all, to the fact that it did not have time to fully recover after the stage of a difficult and protracted period of the global pandemic. Educational institutions were forced to significantly reform and adapt their work to the requirements of quarantine restrictions, conditions of limited communication in the educational institutions themselves and with students. These issues and tasks of guaranteeing safety, reliability, and accessibility of education in such life-threatening conditions were slowly resolved. However, this was only the first test for educators. The functioning of the education system in the conditions of war is an extremely difficult issue, because the preservation of the foundations of the state, its spiritual-mental, cultural, intellectual component depends on it. The purpose of this article is to identify the leading trends and problems of the functioning of higher education in Ukraine. Based on the analysis of data received in response to a request for access to public information, in particular on the number of students in institutions of higher education of the I and II levels of accreditation, the number of students in institutions of higher education of the III and IV levels of accreditation, the teaching staff of higher education institutions, we established structural and dynamic features of higher education in large cities of Ukraine (for example, Kharkiv, Odesa, Dnipro and Lviv) during 2001-2021 as leading centers of higher education. The autrors revealed peculiarities of higher education in Ukraine in the conditions of the Covid-19 pandemic, the features and trends of the functioning of the higher education system in the conditions of a full-scale war and identified the existing problems, challenges, and opportunities for the further development of higher education.